An Industrial systems design study on Alps Cottage Industry Corporation - Angeles, Laureen G. (College of Engineering, 2001)
The study applies the techniques and strategies of supply chain management to the entire logistics system of the Alps Cottage Industry Corporation. The study comprises detailed documentation, problem analysis, generation and evaluation of feasible alternatives, recommendations and its step-by-step implementation. Documentation of the current system includes all components of the inbound and outbound logistics ? purchasing, inventory management, warehousing and stores operations, manufacturing, finished goods inventory, transport operations, and customer service and distribution. This part utilizes several documentation tools such as flow process charts, tables and graphs. With all the necessary information, the study proceeded with the analysis of the performance of the existing system through the use of different performance measures. These performance measures are frequency of rush orders and change orders, space utilization, purchasing cycle time, supplier support, etc. Problems for each component are identified and several criteria are developed to find the company's main problems. From the said problem prioritization strategy, it was concluded that poor distribution, inadequate materials monitoring, unreliable suppliers and lax delivery terms are the main problems of the company. For each of these problems, further analysis of the causes was established through the use of Ishikawa Diagrams. Several feasible alternatives, mostly industry?s best practices were generated for each main problem. These alternatives were evaluated using different criteria based on the priorities identified by the company. The chosen alternatives are presented as recommendations. Recommendations of the study include replacement of the unreliable suppliers, use marketing teams and customer service level measurement, JIT purchasing, and manual bin card system. The study also recommends an general purchasing policy, the use of forms for the inventory monitoring, a supplier evaluation method, the use of different performance measures, color coding for faster stock location and block plans for the storage areas. Step by step implementations for all these recommendations are discussed at the end of the study.